Arm reconstruction with myocutaneous flap of the latissimus dorsi muscle after resection of sarcomas: report of two cases and description of the surgical technique - Leonardo Orletti; Ana Luiza Miranda Cardona; Ana Paula Mazzocco; Marcio Diniz Barreto; Luiz Augusto de Castro Fagundes (Revista Brasileira de Cirurgia Plástica)
Soft tissue sarcomas are rare malignant neoplasms arising from the mesenchyme, most commonly found in the limbs. Surgical resection with free margins greater than 1 cm is essential to obtain a cure for the patient. Radiation therapy can be combined with treatment in selected cases. Reconstruction of the upper limbs after extended resections is a challenge. The latissimus dorsi myocutaneous flap (LDMF) is an option in injuries to the upper limbs, especially the proximal and middle thirds of the arm, with preservation of limb function and primary closure of the resection area. We report two cases of arm resection and reconstruction using LDMF, focusing on the surgical technique description.